Effects of pre-existing damage and cyclic overloading on the flexural behaviour of RC beams strengthened with prestressed CFRP plates. (15th November 2021) - Xie, Jianhe; Li, Jianglin; Lu, Zhongyu; Liu, Di; Huang, Peiyan
Highlights: The post-fatigue behaviour of damaged RC beams strengthened with self-anchored prestressed CFRP plates was investigated. The coupling effects of corrosion- and cyclic overload-induced damage on the flexural of strengthened RC beams were revealed. The roles of load-induced damage and corrosion-induced damage on the time-dependent prestress loss of CFRP-strengthened RC beams were examined. A modified theoretical model that considers the effect of predamage was developed to predict the load-bearing capacity of strengthened RC beams. Abstract: Using prestressed carbon fibre-reinforced polymer (CFRP) plates to strengthen reinforced concrete (RC) members is of particular interest to maintain the safe operation of existing bridge structures. This work aims to assess the effects of existing damage in RC beams before strengthening and overloading after strengthening on the reliability of this strengthening technique. A series of tests were conducted to simulate load- and corrosion-induced damage in RC beams and to investigate the flexural behaviour and post-fatigue behaviour of damaged RC beams strengthened with prestressed CFRP plates in anchor systems. The experimental results revealed that the coupling action of corrosion- and cyclic overload-induced damage remarkably reduced the flexural stiffness of the strengthened RC beams but did not greatly impact the ultimate load of the strengthened RC beams, indicating the effectiveness of the prestressed strengthening system. After exposure to cyclic overloading, the strengthened RC beams containing load- and steel corrosion-induced damage had an ultimate load retention of more than 80% and had a similar failure mode of concrete crushing. The proposed model agrees well with the experimental results, implying that it could conservatively predict the ultimate load of strengthened RC beams after exposure to a low-cycle overload.